Sublingual immunotherapy of atopic dermatitis in mite-sensitized patients: a multi-centre, randomized, double-blind, placebo-controlled study. Issue 1 (4th December 2019) - Liu, Lunfei; Chen, Jisu; Xu, Jinhua; Yang, Qinping; Gu, Chaoying; Ni, Chunya; Li, Linfeng; Lu, Xueyan; Yao, Zhirong; Tao, Jianfeng; Guo, Yifeng; Fang, Hong; et al.
Abstract: Allergen-specific immunotherapy is widely used for allergic rhinitis and asthma treatment worldwide. This study explored the efficacy and safety of sublingual immunotherapy (SLIT) with the extracts of Dermatophagoides Farinae ( D. farinae Drops) on house dust mites (HDM)-induced atopic dermatitis (AD). 239 patients with HDM-induced AD were recruited and exposure to a multi-centre, randomized, double-blind, and placebo-controlled clinical trials for 36 weeks, which were randomly divided into placebo and sublingual D. farinae Drops groups (high-dose, medium-dose and low-dose), respectively. Statistical analysis was performed in three groups: Full Analysis Set, Per Protocol Set and Safety Set. 48 cases have withdrawn from the study before the end of study. As primary outcomes, significant decreases in scoring atopic dermatitis and total medication score were showed in medium-dose and high-dose D. farinae Drops groups. In the sixth visit, the skin lesion area showed a statistically significant difference between high-dose/medium-dose D. farinae Drops group and placebo group ( p < .05). Most adverse events are slight, and no life-threatening adverse drug reaction happened. Our research demonstrates the beneficial effect of SLIT with high or medium dose D. farinae Drops on AD, and the treatment was well tolerated.